Andrographolide, a New Hope in the Prevention and Treatment of Metabolic Syndrome - Islam, Muhammad T. (Frontiers in Pharmacology, 2017)
Recently, the use of plant-derived medicines is increasing interest in the prevention and treatment of a variety of disorders including metabolic syndromes. Metabolic syndrome is one of the major risk factors for cardiovascular diseases (CVDs) and incidence of mortality worldwide. Scientific evidence suggests that Andrographis paniculata and its derived components, especially andrographolide (AGL) and its analogs/derivatives have a broad spectrum of biological activities. This review aims to sketch the activity of AGL and its analogs/derivatives against the components of metabolic syndromes such as diabetes, hyperlipidemia, hypertension, and obesity. Additionally, AGL activity against CVDs is also summarized. The finding suggests that AGL and its analogs/derivatives have a potential role in the management of metabolic syndrome; however, more studies should be conducted to evaluate their effectiveness.